Documentary functions: the uses of documents in non-fictional texts. Issue 1 (1st January 2021) - González, Rayco; Serra, Marcello
Abstract : Among the phenomena that define the spirit of our times, there is a growing tendency towards the registration and storage of data. Included within this phenomenon that some theorists call documentary inflation, the current spotlight on non-fictional narratives gives intelligibility to data and documents. Using some examples taken from documentary cinema as its basis, this article proposes a typology of the uses (or functions) of documents. Four different documentary functions are defined and articulated starting from the logical opposition between syntagmatic and paradigmatic: narrative, referential, systemic and revealing.